SPECIFIC-HEATS OF TYPE-E THERMOCOUPLE WIRES - CHUNG, M; BRILL, JW (AMER INST PHYSICS, 1993)
We report on the specific heats of type E thermocouple wires, constantan (55% Cu-45% Ni) and chromel (10% Cr-90% Ni), measured using ac calorimetry in the temperature range 18-290 K. Data were normalized to values at 200 K determined by differential scanning calorimetry. The constantan values are close to those of other Cu/Ni alloys, while this is the first reported low-temperature result for chromel.
Keywords: TRANSITIONS; CALORIMETRY